Pojok kasih lansia: optimizing the quality of life for older adults in lumajang regency through the development of an elderly-friendly park - Kumboyono, Kumboyono; Dewi, Elvira Sari; Dewi, NI Putu Wahyu Eastiya; Febriano, Luis Figo; Anwar, Mochamad Saiful; Syadilla, Iryne Putri; Setyaningsih, Diva Ayu; Nadhifah, Umi; Rahmat, Basuki; Mayasari, Linda; Fathoni, Jazimah Nur; Kristianingrum, Niko Dima; Swastirani, Astika; Fahanani, Agwin Fahmi (Caring: Jurnal Pengabdian Masyarakat, 2025)
The increasing elderly population in Lumajang Regency, especially in Yosowilangun District, indicates progress in life expectancy but also brings challenges related to elderly care and dependency. To address these issues, a women's empowerment program was conducted in 2023 through the mentoring of Elderly Care Mothers, focusing on promoting elderly independence and caregiver support. In 2024, the initiative continued with the development of a Senior-Friendly Park equipped with ergonomic seating, sensory therapy, and recreational facilities under the concept of the Elderly Care Corner. This program aimed to improve the quality of life of older adults, enhance community involvement, and support caregiving efforts. The activities included park construction, public engagement, capacity-building for elderly care cadres, and the development of educational materials for caregivers. The outcomes demonstrated active participation of 75 elderly individuals within the first two months, a 32 percent increase in knowledge among 20 trained elderly care cadres, and reduced workload reported by 68 percent of caregivers. Improvements were also recorded in quality of life scores, particularly in life satisfaction and daily activities. Qualitative findings highlighted increased social interaction, motivation, and caregiver confidence. This initiative has encouraged replication in other villages and is expected to contribute positively to the well-being of the elderly population in Lumajang Regency.